Bicultural Mentors provide you with global perspectives - Engelhard, Franziska; Ambrosius, Judith (Personalführung, 2016)
With the importance and number of international assignments rising, organizations are increasingly using mentors to support employees during their time abroad. Mentoring during international assignments does hereby not only imply that the mentor possesses functional qualifications, but also combines cultural and psychosocial competencies. Biculturals - people who have internalized multiple cultures - often possess a higher level of these competencies than monoculturals, and can, therefore, provide efficient support during international assignments. Bicultural managers are an important instrument for expatriation

Challenges of foreign inpatriates in the Nürnberg metropolitan region: The case of Vinay Kumar and his family - Nair, Sindhu; Holtbrügge, Dirk; Ambrosius, Judith (Nomos Verlagsgesellschaft mbH und Co KG, 2024)
CRIS-Team Scopus Importer:2025-02-04

Effects of Culture on CSR Practices: Evidence from India. - Garg, Ritam; Ambrosius, Judith (2016 European Academy of Management Meeting, 2016)

Expatriation and Personality Traits: An Empirical Study on the Impact of Mentoring. - Schuster, Tassilo; Ambrosius, Judith; Bader, Benjamin (2016 European Academy of Management Meeting, 2016)

Indian CSR Practices: Mapping the Indigenous Indian Management Concepts for Wider Understanding. - Garg, Ritam; Ambrosius, Judith (2016 Academy of International Business UK and Ireland Chapter Meeting, 2016)

Land der Gegensätze. Herausforderungen für westliche Unternehmen. - Engelhard, Franziska; Ambrosius, Judith (Indien-Contact, 2015)
Im Rahmen eines Forschungsaufenthaltes am Indian Institute of Management in Bangalore besuchte eine Delegation des Lehrstuhls für Internationales Management der Friedrich-Alexander-Universität Erlangen-Nürnberg Unternehmen in Ahmedabad und Bangalore. Ziel der Reise war es, mehr über die alltäglichen Herausforderungen westlicher Firmen in Indien in Erfahrung zu bringen sowie Eindrücke zum kulturellen Umfeld, in dem sich die Unternehmen bewegen, zu gewinne
Keywords: Indien; kulturell Heterogentität; westliche Firmen

Mentoring in International Assignments: A Personality Traits Perspective. - Schuster, Tassilo; Ambrosius, Judith; Bader, Benjamin (2016 Academy of Management Annual Meeting, 2016)

Mentoring, skill development, and career success of foreign expatriates - Holtbrügge, Dirk; Ambrosius, Judith (Human Resource Development International, 2015)

Personality Traits, Mentoring, and Psychological Well-Being: An Investigation of International Assignments. - Schuster, Tassilo; Ambrosius, Judith; Bader, Benjamin (2016 Academy of International Business Annual Meeting, 2016)

Strategic Talent Management in Emerging Markets and its Impact on Employee Retention: Evidence from Brazilian MNCs - Ambrosius, Judith (Thunderbird International Business Review, 2016)

The Effects of Strategic Talent Management on Employees’ Intention to Leave Brazilian MNCs. - Ambrosius, Judith (2015 European International Business Association Annual Meeting, 2015)

The Impact of Formal and Informal Mentoring on Students’ Cultural Intelligence: Evidence from Studies Abroad. - Ambrosius, Judith (2015 Academy of International Business UK and Ireland Chapter Meeting, 2015)